Cholesteric Liquid Crystals: Rationally Designed Dynamic Superstructures Enabled by Photoaligning Cholesteric Liquid Crystals (Advanced Optical Materials 12/2015). Issue 12 (December 2015) - Ma, Ling‐Ling; Li, Sen‐Sen; Li, Wen‐Song; Ji, Wei; Luo, Bin; Zheng, Zhi‐Gang; Cai, Zhi‐Ping; Chigrinov, Vladimir; Lu, Yan‐Qing; Hu, Wei; Chen, Lu‐Jian
Abstract : Helical structures exist universally. Rationally designed cholesteric liquid crystal (CLC) superstructures with arrangements of in‐plane helical axes realized by W. Hu, L.‐J. Chen, and co‐workers result in unique fingerprint textures for potential advanced photonic applications. On page 1691, they describe their digital micromirror device‐based photoalignment technique and demonstrate the growth of spiral and wave‐like continuous gratings, producing CLCs with chirality, depth and integrity, just like our universe.